A Generalized Functional Model Based Method for Vibration-Based Damage Precise Localization in 3D Structures. (June 2015) - Sakaris, Christos S; Sakellariou, John S; Fassois, Spilios D
Abstract: A Generalized Functional Model Based Method for vibration-based damage precise localization on structures consisting of 1D, 2D, or 3D elements is introduced. The method generalizes previous versions applicable to structures consisting of 1D elements, thus allowing for 2D and 3D elements as well. It is based on scalar (single sensor) or vector (multiple sensor) Functional Models which - in the inspection phase - incorporate the mathematical form of the specific structural topology. Precise localization is then based on coordinate estimation within this model structure, and confidence bounds are also obtained. The effectiveness of the method is demonstrated through experiments on a 3D truss structure where damage corresponds to single bolt loosening. Both the scalar and vector versions of the method are shown to be effective even within a very limited, low frequency, bandwidth of 3-59 Hz. The improvement achieved through the use of multiple sensors is also demonstrated.